2021
DOI: 10.3389/fonc.2021.606915
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Organic Compounds in Human Exhaled Breath to Diagnose Gastrointestinal Cancer: A Meta-Analysis

Abstract: IntroductionHuman exhaled volatile organic compounds (VOCs) are being extensively studied for the purposes of noninvasive cancer diagnoses. This article was primarily to assess the feasibility of utilizing exhaled VOCs analysis for gastrointestinal cancer (GIC) diagnosis.MethodsPRISMA-based system searches were conducted for related studies of exhaled VOCs in GIC diagnosis based on predetermined criteria. Relevant articles on colorectal cancer and gastroesophageal cancer were summarized, and meta analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 62 publications
(89 reference statements)
0
22
0
Order By: Relevance
“…The shifts in CRC-associated gut microbiota composition and activity might translate into measurable outcomes in the human VOC profile. Several studies have identified altered VOC profiles associated with CRC and, to a lesser extent, colorectal adenomas, when compared to (healthy) controls [ 22 , 23 , 24 ]. VOCs of interest for CRC detection have previously been categorized as those originating from altered cell energetics, alterations in enzymatic activity of cancerous cells, and oxidative stress in a review by Monedeiro et al [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The shifts in CRC-associated gut microbiota composition and activity might translate into measurable outcomes in the human VOC profile. Several studies have identified altered VOC profiles associated with CRC and, to a lesser extent, colorectal adenomas, when compared to (healthy) controls [ 22 , 23 , 24 ]. VOCs of interest for CRC detection have previously been categorized as those originating from altered cell energetics, alterations in enzymatic activity of cancerous cells, and oxidative stress in a review by Monedeiro et al [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The vast discrepancies among material types strongly suggest this part of the research is still empirical and needs better understanding, characterization, and standardization. In the future, this field of research would benefit from a better description of material parameters, as it is often done in publications reporting VOC detection by GC-MS. 117,118 4.2.5. Sample conservation.…”
Section: Odor Sampling Materials All Types Of Body Matricesmentioning
confidence: 99%
“…Other VOCs are emitted in the biological processes occurring in human bodies [ 41 , 42 , 43 ]. For example, it has been observed that breath samples from breast cancer patients contain a unique combination of hydrocarbons, such as alkanes and monomethylated alkanes [ 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%